2013
DOI: 10.1245/s10434-013-2984-8
|View full text |Cite
|
Sign up to set email alerts
|

Should an Involved but Functioning Recurrent Laryngeal Nerve be Shaved or Resected in a Locally Advanced Papillary Thyroid Carcinoma?

Abstract: Our data suggested that shaving could preserve the normal functionality in most of the involved RLNs (>90%) in the short to medium term. In the presence of distant metastases or incomplete resection in other non-RLN concomitant sites, the argument for shaving over resection appears even stronger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 15 publications
2
37
1
Order By: Relevance
“…Some articles showed no prognostic difference if the affected nerve was either completely resected or when the nerve itself was preserved and the tumor tissue was macroscopically radically removed [13, 17, 18]. However, these studies were retrospective, with a small number of patients and a short follow-up or with nonhomogeneous distribution of extrathyroidal involvement in the compared groups.…”
Section: Prognostic Significance Of the Rln Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Some articles showed no prognostic difference if the affected nerve was either completely resected or when the nerve itself was preserved and the tumor tissue was macroscopically radically removed [13, 17, 18]. However, these studies were retrospective, with a small number of patients and a short follow-up or with nonhomogeneous distribution of extrathyroidal involvement in the compared groups.…”
Section: Prognostic Significance Of the Rln Involvementmentioning
confidence: 99%
“…Lang et al retrospectively compared results of 39 and 38 patients, respectively, with the PTC infiltrating the RLN and demonstrated improved short-term and long-term results equally, if the RLN is released from the tumor (by shaving), compared with the radical resection of the infiltrated laryngeal nerve [13]. These two groups were not homogeneous.…”
Section: Prognostic Significance Of the Rln Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [6][7][8] have revealed that involvement of RLN had no significant influence on survival, while local invasion to the trachea, larynx, and esophagus [3,5] showed a significant correlation with survival.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of preserving an RLN that is functioning but has cancer involvement, followed by the use of adjuvant treatments such as radioactive iodine (RAI) ablation or radiation therapy has been supported by several studies [6][7][8]. However, these studies enrolled patients with relatively inhomogeneous clinical characteristics including patients with preoperative vocal cord paralysis (VCP), concomitant involvement of non-RLN structures, distant metastasis on initial presentation, and involvement of RLN with recurrent metastatic lymph node (LN).…”
Section: Introductionmentioning
confidence: 99%